BM-MSCs alleviate diabetic nephropathy in male rats by regulating ER stress, oxidative stress, inflammation, and apoptotic pathways - Khamis, Tarek; Abdelkhalek, Adel; Abdellatif, Hussein; Dwidar, Nourelden; Said, Ahmed; Ahmed, Rama; Wagdy, Kerolos; Elgarhy, Rowina; Eltahan, Rawan; Mohamed, Hisham; Said Amer, Eman; Hanna, Maria; et al. (Frontiers in Pharmacology, 2023)
Diabetic nephropathy (DN), a chronic kidney disease, is a major cause of end-stage kidney disease worldwide. Mesenchymal stem cells (MSCs) have come into beingbecome a promising option to mitigate several diabetic complications. In this study, we evaluated the therapeutic potential of bone marrow-derived mesenchymal stem cells (BM-MSCs) in a rat model of STZ-induced DN. 45 male Sprague-Dawley rats were randomly assigned to one of three groups; control, STZ-induced DN, and BM-MSC-treated STZ-induced DN. A single intraperitoneal dose of STZ was used to induce type 1 diabetes in rats. After the confirmation of diabetes, rats were treated with BM-MSCs and sacrificed at week 12 after treatment. Our results showed that STZ-induced DN rats had extensive histopathological changes, significant upregulation in mRNA expression of renal apoptotic markers, ER stress markers, inflammatory markers, fibronectin, and intermediate filament proteins, and re-duction of positive immunostaining of PCNA and elevated P53 in kidney tissue compared to the control group. BM-MSC therapy significantly improved renal histopathological changes, reduced renal apoptosis, ER stress, inflammation, and intermediate filament proteins, as well as increased positive immunostaining of PCNA and reduced P53 in renal tissue compared to the STZ-induced DN group. In conclusion, our study indicates that BM-MSCs may have therapeutic potential for the treatment of DN as well asnd provide important insights into their potential use as a novel thera-peutic approach for DN.